Material composition – Pinning strength correlation in Nb thin films with focused ion beam-milled washboard nanostructures - Dobrovolskiy, O.V.; Begun, Evgenia; Huth, M.; Shklovskij, V.A. (Physica C, 2013)
An analysis of the interrelated changes in the material composition and the pinning strength in nanostructured Nb (110) thin films is presented. The nanopatterns were prepared by focused ion beam milling of an array of uniaxial grooves. They induce a washboard-like pinning potential landscape for vortices in the mixed state. By applying different magnetic fields, the most likely pinning sites along which the flux lines move through the samples have been selected. By this, either the background isotropic pinning of the pristine film or the enhanced isotropic pinning originating from the nanoprocessing has been probed. The enhanced pinning strength in the processed films has been found to correlate with the content of Ga implanted into the films during the nanopatterning.
Keywords: Research Subject Categories::NATURAL SCIENCES